Timing in symphony orchestras, the relative importance of sight and hearing - Lidar, Emma (My University, 2016)
The influence of sight and common internal pulse on the musicians experience of stage acoustics are not much investigated. Many acoustic parameters based on impulse response measurements are available to describe the room but few of them correlate well with the musicians’ own experiences. This thesis focuses on timing for symphony orchestras. Timing is an important part of stage acoustics for symphony orchestras. The goal for the musicians is that the instruments shall sound tightly synchronised for the audience. Large distances between musicians in symphony orchestras may create sound delays up to 60 ms between different instrument groups and to the audience. If the musicians use hearing, without seeing each other and referring to their internal feeling of pulse, this would result in bad synchronisation and retarding tempo. The senses sight and hearing are investigated to see the relative importance for timing when removing one or both of them. When removing both, the musicians need to trust their own internal pulse. Subjective tests are made with the University of Gothenburg Symphony Orchestra. The orchestra is recorded when playing a piece especially written for this occasion and a piece by Mozart. Onset of every tone is detected and compared to each other, to see the level of synchronicity. The studies show larger deviations between musicians when playing with just sight than with just hearing but both senses are needed to get the best timing. When removing both sight and hearing other cues are used to be able to play in synchrony and vibrations from the bass section were more noticed by musicians in other sections. Different seating arrangements are tested and the the setup where the orchestra sits closest together improve timing in all settings. This investigation indicate that many senses influence the ability to synchronise. Therefore, acoustic measurements alone can not explain the features of the stage,at least not when it comes to playing synchronised.
Keywords: Akustik; Building Futures; Acoustics; Building Futures